ABNORMAL STING-RAY CAUGHT OFF CALICUT - Nair, K V Somasekharan; Chellam, A (Indian Journal of Fisheries, 2011)
An abnormal male specimen of the sting-ray Himantura uarnak caught in the trawlnet at Calicut is described. The anterior lobes of the pectoral fins were not fused withthe head and were tapering forward and inward in the form of a pair of horns.